Mode-I Fracture Energy Influence on the Behavior of Plain Concrete Beam - Albayyati, Mehdi Ali Jawad (Basrah Journal for Engineering Sciences, 2013)
The principle aim of this research is concentrated to analyze the effect of cracks and their propagations on the mechanical behavior of a quasi-brittle material such as concrete. The singularity (stress concentration to infinity at the tip of crack) is avoided by using the principal of fracture energy with the fictitious crack approach. The concrete crack is divided into two major zones; the first one is the fracture zone (a combination of bridging effect and the cohesive microscopic cracking) which obeys a special law permitting the transmission of stress across the two faces of crack, this zone is considered as partially cracked concrete. When the opening of the crack exceeds a specific value, this zone is converted to a real crack (an open crack) and cannot transmit any stress across the two faces of a crack. The program of finite element used in this research is prepared by the researcher using discrete-crack approach with the experimental data obtained from the flexural test on notched beam loaded under three-point bending, where fracture mode I is dominated. The response of the applied load-crack mouth opening displacement (CMOD) with appropriate fracture energy is selected. The results show that the cohesive microscopic cracking zone for the plain concrete is very wide. The cohesive stress distributions across the microcracks with the corresponding crack openings are drawn from the first crack appearance till the beam failure.